Clinical and psychological correlations with type D personality in patients with chronic coronary syndrome - A. N. Sumin; A. V. Shcheglova; M. I. Anichkova; D. N. Fedorova; K. A. Shabalina (Acta Biomedica Scientifica, 2023)
Recently, it has become common to identify type D personality, which is predisposed to the development of psychological distress. Negative behavioral characteristics of individuals with type D personality contribute not only to the development of cardiovascular diseases, but also to  other comorbid pathologies that can influence the progression and prognosis of coronary heart disease. The aim of the study. To identify clinical and psychological correlations with type D personality in patients with chronic coronary syndrome. Methods. The study included 113 patients (68 men and 45 women; median age – 64 years) admitted for planned percutaneous coronary intervention at the Research Institute for Complex Issues of Cardiovascular Diseases (Kemerovo, Russian Federation). Based on the results of the DS-14 test, patients were divided into two groups: patients with type D personality (n = 40) and patients without this type (n = 73). Results. In patients with chronic coronary syndrome with type D personality, compared with patients without this type, concomitant diabetes mellitus (35 % and 15 %, respectively; p = 0.018), signs of diastolic dysfunction of left (Е/е’ ratio 7.1 [6.48; 8.0] and 5.0 [4.55; 5.74], respectively; p = 0.0038) and right (Et/At ratio – 0.8 [0.66; 1.35] and 1.38 [1.28; 1.63], respectively; p = 0.014) ventricles were more often diagnosed. Correlation analysis revealed associations of diabetes mellitus with type D personality (r = 0.243; p = 0.011), severity of negative excitability (r = 0.253; p = 0.008) and social suppression (r = 0.224; p = 0.020), as well as association of ankle-brachial index (ABI) with the severity of negative excitability (r = 0.393; p = 0.004) and social suppression (r = 0.414; p = 0.002). Conclusion. In patients having chronic coronary syndrome with type D personality, concomitant diabetes mellitus, as well as left and right ventricular filling disorders are  more often detected. Correlation analysis revealed associations of diabetes mellitus with type  D personality and its subscales; the ABI level was associated with subscales of type D personality, but not with the level of anxiety and depression.